Psychological aspects of injury in gymnastics - Shapiro, J. L.; Bartlett, M. L.; Lomonte, L. E. (Gymnastics medicine - evaluation, management and rehabilitation, 2020)
While many sports medicine professionals (e.g., medical doctors, physical therapists, athletic trainers, chiropractors, massage therapists) focus on the physical aspects of injury recovery, the psychological effects of sport injury and impact on recovery also warrant attention by medical providers. Psychological factors can increase or decrease the risk of injury occurring, can impact an athlete's emotional and behavioral response to injury, and can affect the recovery process. Psychological interventions, such as mental skills interventions, can both prevent injury and enhance injury rehabilitation and return to sport. When emotional disturbances and clinical issues (e.g., major depression, anxiety, eating disorders, substance abuse, trauma) are present, sports medicine professionals should refer athletes to a qualified mental health professional. This chapter addresses (a) psychological and socio-cultural antecedents of injury; (b) psychological responses to injury; (c) psychological interventions during rehabilitation; and (d) psychological aspects of returning to gymnastics following injury. The referral process to mental health professionals and multidisciplinary treatment of the injured athlete will also be discussed.